2020
DOI: 10.2174/0929867326666190726121711
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Advances in the Treatment of Age-related Macular Degeneration

Abstract: Age-related macular degeneration is an acquired degenerative disease that is responsible for severe loss of vision in elderly people. There are two types: dry age-related macular degeneration and wet age-related macular degeneration. Its treatment has been improved and tries to be tailored in the future. The aim of this review is to summarize the pharmacological advances in the treatment of age-related macular degeneration. Regarding dry AMD, there is no effective treatment to reduce its progression. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 87 publications
0
26
0
Order By: Relevance
“…Neovascularization is driven primarily by an increase in vascular-endothelial growth factor (VEGF). Most available anti-AMD treatments are designed to reduce or slowdown neovascularization, using monoclonal antibodies against VEGF or its receptor (Gil-Martinez et al, 2020). However, there is currently no treatment that can prevent or stop the death of photoreceptors, let alone reverse it.…”
Section: Introductionmentioning
confidence: 99%
“…Neovascularization is driven primarily by an increase in vascular-endothelial growth factor (VEGF). Most available anti-AMD treatments are designed to reduce or slowdown neovascularization, using monoclonal antibodies against VEGF or its receptor (Gil-Martinez et al, 2020). However, there is currently no treatment that can prevent or stop the death of photoreceptors, let alone reverse it.…”
Section: Introductionmentioning
confidence: 99%
“…45 Other longer acting protein therapies that are in clinical trials include abicipar pegol (Allergan) and ForSight VISION4's port delivery system (PDS) for ranibizumab (Genentech). 22,46 Phase IIII studies (HAWK and HARRIER) showed 12 week treatment interval with brolucizumab, a humanised single chain variable antibody fragment of 28 kDa. A 6.0 mg intravitreally injected dose of brolucizumab has been shown to be non-inferior in the mean change in best-corrected visual acuity from baseline to an 8 week treatment interval with aflibercept for wAMD.…”
Section: Clinical Need For Longer Acting Therapiesmentioning
confidence: 99%
“…51 Abicipar pegol is a PEGylated conjugate of a type of protein known as a Designed Ankyrin Repeat Protein (DARPin). 22 The CEDAR and SEQUOIA trials showed abicipar pegol at 8 or 12 week dosing to be non-inferior to Lucentis ® 4 week dosing for wAMD. 52 The PDS allows a continuous delivery of ranibizumab to the vitreous 53 from a non-biodegradable system 54 and is currently in Phase III clinical trials.…”
Section: Clinical Need For Longer Acting Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Huan et al reported silica‐supported silver nanoparticles as solid, recyclable catalysts for Diels−Alder cycloadditions of 2′‐hydroxychalcones and dienes in high yield and turnover number. Maria et al reported that copper nanoparticles supported on activated carbon catalyzed the multicomponent synthesis of indolizines from pyridine‐2‐carbaldehyde derivatives, secondary amines, and terminal alkynes in dichloromethane. All the above reported reactions use a highly expensive catalyst and nongreen solvents.…”
Section: Introductionmentioning
confidence: 99%